Eruptive cutaneous sarcoidosis – A rare phenomenon - Badash, Almog; Zimmerman, Lacey; Hirsch, Yonatan; Sweiss, Nadera; Haber, Roger (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
This case highlights an unusually rapid onset and extensive presentation of eruptive cutaneous sarcoidosis in a 61-year-old woman who developed a sudden, widespread pruritic rash overnight after ingesting a supplement containing black seed oil and vitamins D3, K2, and E. She responded well to corticosteroid treatment. We compared the findings with two other cases found in the literature. This type of presentation has not been previously documented.